Robust micropropagation protocol for genetically true to type plants of Phule Arakta pomegranate - Raman, Taramla; Gupta, Vidya S.; Shukla, Susmita (Indian Journal of Horticulture, 2019)
A rapid and reproducible micropropagation protocol for pomegranate cv. Phule Arakta has been developed using nodal segments of field grown plant. Bud break was induced in basal Woody Plant Medium (WPM) as well as compared when WPM was supplemented with plant growth regulators. Multiple shoot proliferation was induced in the nodal segments on WPM fortified with different concentration of benzyladenine (BAP) where 2mg/I BAP developed maximum number of shoots. Elongation of shoots was further amplified with the addition of adjuvant silver nitrate. Browning of culture medium was controlled by the addition of polyvinylpyrrolidone (PVP) and regular sub-culturing enhanced shoot multiplication as well as elongation. Rooting was induced in the regenerated shoots using Indole-3-butyric acid (IBA) and 3-Indoleacetic acid where best result was obtained using shock treatment with NAA. Sub-culturing resulted in denser and better rooting. The rooted plantlets were further acclimatized and then established in soil. The clonal fidelity of the in vitro grown cultures was assessed using Random Amplified Polymorphic DNA (RAPD) and Inter Simple Sequence Repeats (ISSR) markers. The 10 RAPD decamers produced 55 bands and 4 ISSR produced 19 bands in total. RAPD primers OPC-08, OPC-13 and OPD-07 produced the highest number of distinct bands and ISSR primer UBC-834 produced maximum distinct bands. All the bands were monomorphic which confirms the genetic fidelity of the in-vitro raised P. granatum cv. Phule Arakta and supported the method of mass production of true to type progenies using tissue culture.
Keywords: genetic fidelity; ISSR; Punica granatum; RAPD